2004
DOI: 10.1111/j.0022-202x.2004.23224.x
|View full text |Cite
|
Sign up to set email alerts
|

Proliferating Keratinocytes Are Putative Sources of the Psoriasis Susceptibility-Related EDA+(Extra Domain A of Fibronectin) Oncofetal Fibronectin

Abstract: The extra domain A of fibronectin (EDA+ oncofetal isoform of fibronectin was recently reported to be overexpressed in psoriatic uninvolved epidermis. It has been proposed that the abnormal presence of EDA+ oncofetal protein at the dermal-epidermal junction in the uninvolved skin may provide the "psoriatic" environment in which keratinocytes are in a preactivated state with regard to mitogenic signals (e.g., T cell lymphokines). To determine the possible sources of cellular fibronectin in the non-lesional psori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 31 publications
9
44
0
1
Order By: Relevance
“…These results suggest that PRINS overexpression plays a role in psoriasis susceptibility and not in the precipitation of psoriatic symptoms. Moreover, these observations are in agreement with previous results showing that keratinocytes in the uninvolved skin of psoriatic patients differ from healthy keratinocytes in their responses to external stimuli (14,21,22). The overexpression of PRINS in the psoriatic uninvolved epidermis may reflect an altered regulatory extracellular milieu, but it is also possible that PRINS plays a regulatory role in the hyperproliferation of keratinocytes in psoriasis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results suggest that PRINS overexpression plays a role in psoriasis susceptibility and not in the precipitation of psoriatic symptoms. Moreover, these observations are in agreement with previous results showing that keratinocytes in the uninvolved skin of psoriatic patients differ from healthy keratinocytes in their responses to external stimuli (14,21,22). The overexpression of PRINS in the psoriatic uninvolved epidermis may reflect an altered regulatory extracellular milieu, but it is also possible that PRINS plays a regulatory role in the hyperproliferation of keratinocytes in psoriasis.…”
Section: Discussionsupporting
confidence: 92%
“…Because the primer pair we used to detect the fibronectin mRNA abundance was designed to border the EDA motif of fibronectin, we were able to detect both the EDA Ϫ and EDA ϩ isoforms of fibronectin (Fig. 1B) as well as changes in the ratio of these two isoforms (22). The novel cDNA, AK022045, showed the highest level of expression in the serum-starved, contact-inhibited HaCaT keratinocytes (0 h sample), and as the cells started to proliferate because of passaging and serum readdition, the abundance of AK022045 cDNA dropped dramatically (24 -96 h samples) and did not seem to increase even after 168 h, in the confluent culture (Fig.…”
Section: The Identified Transcripts Show Differential Regulation Durimentioning
confidence: 99%
“…Western Blotting-Keratinocytes were incubated with or without DEX (0.1 M) for 0, 1, 24, 48, and 72 h, and total protein extracts were obtained for each time point using a standard protocol (28). 25 g of each protein extract was electrophoresed in a 7.5% SDS-polyacrylamide gel and transferred onto a nitrocellulose membrane (BioScience).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we identified a novel non-coding RNA, PRINS that is expressed at higher level in the non-involved epidermis of psoriatic patients than in either the psoriatic involved epidermis or epidermis of healthy individuals [37]. Our results suggest that the overexpression of PRINS in the non-involved psoriatic epidermis may play role in psoriasis susceptibility [37] and are in accordance with previous studies that in response to external stress stimuli, the keratinocytes of the non-involved psoriatic and of the healthy epidermis answer differentially [182,183]. We additionally showed that the expression of the anti-apoptotic G1P3 gene is under the contol of PRINS [148] and PRINS might interact physically with the molecular chaperone protein nucleophosmin in keratinocytes [148].…”
Section: Discussionsupporting
confidence: 91%